Information System Development for The Service Improvement and Its Effectiveness at PUSBIS UINSA - Millah, Aslihatul; Aziz, M. Abdul; Saraswati, Tsania; Biyanti, Pipit Merit; Siraj, Taufik (Proceeding International Conference on Science and Engineering, 2020)
Many companies or agencies are aware of the role of information technology as a supporter to achieve their vision, mission, and goals nowadays. In 2013, IAIN Sunan Ampel Surabaya changed its name to UINSA and its financial management system is regulated in BLU. This indicates that UINSA must become a self-supporting college financially and increase its income. Reviewing these phenomena, this research would like to develop an information system/application management information system for the PUSBIS of UINSA which focusing on PUSBIS center, Greensa.in, and public facility. The purpose of this study is to know how to develop the information system and its effectiveness in improving service usage of assets / public facilities in UINSA. For that, this research uses the R&D method. The R & D used in this research is R & D level 4 due to this paper will research and develop new products. The results of this study are the settled information system and its statements that information systems that have been built to improve services in lending/usage of assets in PUSBIS.